ANALISIS KOMUNIKASI PERSUASIF PENGELOLAAN BANK SAMPAH KAMPUNG AMPERA RW 09 PADEMANGAN BARAT - Nuraini Diniyanti Morib; Muhammad Fikri Gissani (Faculty of Social and Political Sciences, Universitas Swadaya Gunung Jati, 2025)
The increasing volume of waste in DKI Jakarta necessitates effective waste management strategies. Waste banks are one of the programs utilized for waste management in DKI Jakarta. This study aims to identify, analyze, and evaluate the persuasive communication strategies employed by the managers of the Kampung Ampera RW 09 Pademangan Barat waste bank in enhancing public awareness and participation in waste management. A qualitative approach with a descriptive qualitative design was utilized, incorporating purposive sampling for subject selection and interviews for data collection. The findings indicate that the persuasive communication strategy, which encompasses cognitive, affective, and conative aspects, effectively enhances knowledge, fosters positive attitudes, and promotes behavioral changes among the community in waste management.